Role of vascular plant resources in the lower montane zone in relation to the flora of a mountain and its adjacent area: the South Base of Mt. Babia Góra (Western Carpathians) - Stachnowicz, Wojciech (Biodiversity: Research and Conservation, 2007)
The article is the first scientific summary of contemporary flora of vascular plants growing within the S base of Mt. Babia Góra. It presents main statistics concerning general aspects of species richness, its taxonomical structure and spatial distribution (within 54 squares of 0.25 km2 each). Native vs. anthropogenic origin of species is considered in relation to the neighbouring Babia Góra National Park, as well as the Orawian Hills investigated ca. 30 years ago. The problem of local frequency of taxa is also discussed in relation to general species richness within the investigated area. The enclosed full register of recorded species accompanied by some individual characteristics, such as e.g. frequency of each plant, mountain vs. lowland status etc. provides necessary background for further studies and may enable potential estimation of future changes in the flora of this area, as well as the neighbouring Babia Góra National Park. The investigated flora of the lower montane zone comprised 498 species (439 of which were native), 258 genera and 79 families. These numbers represented the following parts of the neighbouring national park’s taxonomic diversity: 79.6% of its species richness, 89.3% of genera and 96.3% of families. In the light of clearly high contribution of the investigated area to the flora of the whole massif, also considering relatively low share of alien taxa (only 39 permanently established species; i.e. 7.8% of the flora) the lower montane zone deserves effective protection, preferably by including it entirely into the national park.